1993
DOI: 10.1111/j.1440-1738.1993.tb00078.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical Th‐U‐total Pb isochron ages of Jiaodong and Jiaonan metamorphic rocks in the Shandong Peninsula, eastern China

Abstract: The chemical Th-U-total Pb isochron method (CHIME) was applied to determine the age of monazite and thorite in five gneisses and zircon in an ultra high-pressure (UHP) phengite schist from the Su-Lu region, easttrn China. The CHIME ages and isotopic ages reported in the literature show that gneisses in the Su-Lu region are divided into middle Proterozoic (1500-1720 Ma) and Mesozoic (100-250 Ma) groups. The Proterozoic group includes paragneiss and orthogneiss of the amphibolite-granulite facies, and their prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…However, Jahn et al (1988) proposed another developing history for the Taishan Group by the geochemical and isotopic data: (i) the initial basaltic and tenalitic magmas emplaced at 2700-2750 Ma and they were metamorphosed to the amphibolite and grey gneiss, respectively, shortly after their emplacement; (ii) granitic association intruded into the basement during 2400-2600 Ma; and (iii) all Taishan Group members suffered a second metamorphism around 2000 Ma. The data reported in this paper and those of Enami et al (1993a) show that the LP Jiaodong Group is slightly younger than the metamorphic and migmatitic rocks of the Taishan Group.…”
Section: Rb-sragedatamentioning
confidence: 51%
See 1 more Smart Citation
“…However, Jahn et al (1988) proposed another developing history for the Taishan Group by the geochemical and isotopic data: (i) the initial basaltic and tenalitic magmas emplaced at 2700-2750 Ma and they were metamorphosed to the amphibolite and grey gneiss, respectively, shortly after their emplacement; (ii) granitic association intruded into the basement during 2400-2600 Ma; and (iii) all Taishan Group members suffered a second metamorphism around 2000 Ma. The data reported in this paper and those of Enami et al (1993a) show that the LP Jiaodong Group is slightly younger than the metamorphic and migmatitic rocks of the Taishan Group.…”
Section: Rb-sragedatamentioning
confidence: 51%
“…Ten samples were collected for dating a t a road-side outcrop (N37 O 02 ' 44", E l 2 0 40 ' 07"), about 10 km north of Laiyang. Enami et al (1993a) reported a monazite CHIME age of 1620+60 Ma from this locality (their sample No. 92HHOlc) and ascribed the age to the LP/MP metamorphic event.…”
Section: Description Of the Dating Samplesmentioning
confidence: 96%
“…Post‐collisional Mesozoic granites intruded all lithologies of the UHP and HP belts. Protolith ages of eclogite and country rocks are considered to be Proterozoic (Lu et al 1987; Enami et al 1993; Ishizaka et al 1994; Jahn et al 1994). The Sm–Nd isochron ages of eclogites from the Su‐Lu region range from 210 to 230 Ma (Li et al 1993, 1996) and are interpreted to date the peak of metamorphism.…”
Section: Geological Outlinementioning
confidence: 99%
“…No eclogite has yet been found in this area, although rare spinel lherzolite exists (Ishizaka et al, 1994). Rb-Sr whole-rock and chemical Th-U total Pb dating of high-grade gneisses, including hornblende-granulite and migmatitic gneisses, yield mid-Proterozoic (1500 to 1800 Ma) ages (Enami, Suzuki et al, 1993;Ishizaka et al, 1994). Similar ages were obtained by Sm-Nd dating of granulite in this area (Li et al, 1997), and these are compatible with the age of the North China craton (e.g., Wang 1986).…”
Section: Division Of the Shangdong Peninsula And The Sulu Terranementioning
confidence: 98%